2002
DOI: 10.1046/j.1525-139x.2002.00028.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Demographic Aspects of Treated End‐Stage Renal Disease in the Elderly

Abstract: Over the last 10 years an increasing number of patients worldwide have started dialysis or had transplantation. Many are elderly with complex comorbid conditions. Registries across the world all show a rapid and dramatic increase in the number of older patients accepted for renal replacement therapy. In addition, the number of patients who grow old on dialysis is increasing, leading to a marked change in the demographics of the renal population. Changes over time and across registries are discussed with refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 14 publications
(16 reference statements)
1
28
1
Order By: Relevance
“…Survival at 1 year was similar to that seen in our study; however, further data are not available because of the limited follow-up. Other studies have shown shorter survival among older patients than among younger patients, even after correction for multiple comorbid conditions, [10][11][12][13][14] although few compared survival over time for a specific age group, as we did. Our finding of improved survival over time is in contrast to that from a recent study in the United States involving patients aged 80 years or older at the start of dialysis.…”
mentioning
confidence: 54%
“…Survival at 1 year was similar to that seen in our study; however, further data are not available because of the limited follow-up. Other studies have shown shorter survival among older patients than among younger patients, even after correction for multiple comorbid conditions, [10][11][12][13][14] although few compared survival over time for a specific age group, as we did. Our finding of improved survival over time is in contrast to that from a recent study in the United States involving patients aged 80 years or older at the start of dialysis.…”
mentioning
confidence: 54%
“…Centers that are expert in one form of dialysis only cannot present the patient with all his/ her options because, of necessity, they will emphasize the option with which they are most familiar. Also, in presenting the various dialysis options to new patients, physicians and other health-care professionals must avoid imposing their own biases on their patients [2]. Although several surveys indicate that nephrologists agree that we make excessive use of incenter HD, they also regard many factors to be contra-indications to PD [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Increased longevity, coupled with technical advances and heightened public expectation, has contributed to an unprecedented increase in demand for dialysis therapies in older age groups (2). The burden of comorbid disease is higher in this group of patients (4) and has been clearly shown to affect survival (5). For a select group of elderly patients with a heavy burden of comorbid illness, although dialysis may be technically feasible, the short-term mortality is often very high, particularly in those with advanced cardiovascular disease and/or diabetes (6).…”
mentioning
confidence: 99%